ANALISIS AMPLITUDE VERSUS OFFSET (AVO) MENGGUNAKAN PARAMETER PETROFISIKA LAMBDA MU RHO (LMR) DAN EXTENDED ELASTIC IMPEDANCE (EEI) UNTUK KARAKTERISASI RESERVOAR KARBONAT - Harsano Jayadi; Icha Untari Meidji; Yusniati H Muh Yusuf (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
The research that refers to the characterization of carbonate reservoir to identify lithology and fluid had been done to the Baturaja Formation in South Sumatera Basin. The method used is analyzed of Amplitude Versus Offset (AVO) by utilizing the petrophysics parameter of Lambda Mu Rho (LMR) and Extended Elastic Impedance (EEI). The goal of the research is to find out the comparison of the application of petrophysics parameter LMR and EEI to characterization carbonate reservoir, besides finding a prospect location or proposed well. The result of data analysis of Al-Fatah well shows that the carbonate reservoir position with liquefied gas is located deeper around 350 meters with a thickness of around 7.62 meters. Interpretation of seismic from inversion result by using the petrophysics parameter of LMR and EEI shows the presence of a prospect location to the CDP 4253 up to 4301, which is carbonate reservoir with fluid accumulation (gas).